Phase Transition Enthalpy, and Oxidation Binding Energy of Hydrothermally Synthesized BaTiO3 Nanopowders via Pre-annealing and Sintering Processes - J. Lee; J. Jeong; J. Jung; H. Jeong (Archives of Metallurgy and Materials)
Hydrothermally synthesized BaTiO3 nanopowders pre-annealed at high temperatures of 900℃ for 4 h in the air were sintered at 1200℃ for 2 h in N2 atmosphere, and their cubic-tetragonal transformation, transition enthalpy, and binding energy (BE) were investigated. The nanopowder crystal structures changed from cubic to tetragonal during annealing or sintering at temperatures above 900℃ with constant tetragonality (1.01). With increasing pre-annealing temperature, the cubic-tetragonal transition enthalpy decreased, and the differential scanning calorimetry (DSC) peak broadened. Pre-annealing in the air increased BE and nonchemical energy distribution in the BaTiO3 powder, reducing the transition enthalpy and sharpness of the DSC curve. This was ascribed to the differences in imperfections from oxidation, such as the density and uniform distribution of Ba among the samples, resulting from the BE shifts of the Ba 3d, Ti 2p and O 1s peaks to higher values in the XPS spectra.